Ways to Improve the Competitiveness of Industrial Products of the Republic of Kazakhstan - Ukubassova Galiya; Galiyeva Alma; Zambinova Gulmira; Taskimbayev Adil (SHS Web of Conferences, 2025)
This study examines methods to enhance the competitiveness of industrial products in Kazakhstan, emphasizing their role in economic recovery and foreign exchange earnings. The primary aim is to analyze the key factors affecting production efficiency, product quality, and market competitiveness, drawing on international best practices. The study identifies a research gap in the integration of innovative strategies for improving product competitiveness beyond quality, considering factors related to enterprises and national policies. The results highlight that while product quality remains a fundamental component, competitiveness is also influenced by sales strategies, production efficiency, and state-level economic policies. Empirical findings suggest that enterprises must adopt innovative approaches to consumer engagement and market positioning to sustain competitiveness in the global market. The implications of this study are significant for both policymakers and industrial enterprises, offering insights into enhancing production efficiency and aligning industrial strategies with market demands. By addressing the increasing competition in the domestic and international markets, this research contributes to developing a strategic framework for improving the industrial sector’s resilience and growth. The findings provide a foundation for further studies on economic policies and industrial competitiveness, emphasizing the need for innovation-driven production strategies in Kazakhstan.